Vitruvianism : Origins and Transformations - Sanvito, Paolo (Transformationen der Antike, 2015)
Vitruvius' De architectura, the only extant work from Antiquity dedicated to Architecture, has had a rich and diverse reception history. The present volume aims to highlight the different aspects of this history, showing how Vitruvius' work was systematically and continuously misunderstood to justify innovation. Its comprehensive and in-depth analyses make this book a reference work in the field of Vitruvian scholarship.